Effects of starting cellular material composition on chimeric antigen receptor T‐cell expansion and characteristics. Issue 5 (11th April 2019) - Elavia, Nasha; Panch, Sandhya R.; McManus, Andrew; Bikkani, Thejaswi; Szymanski, James; Highfill, Steven L.; Jin, Ping; Brudno, Jennifer; Kochenderfer, James; Stroncek, David F.
Abstract : BACKGROUND: When manufacturing chimeric antigen receptor (CAR) T cells using anti‐CD3/anti‐CD28 beads, ex vivo T‐cell expansion is dependent on the composition of leukocytes used in the manufacturing process. We investigated the effects of leukocyte composition on CAR T‐cell expansion and characteristics using an alternative manufacturing method. METHODS: Anti–B‐cell maturation antigen and CD19‐CAR T cells were manufactured using autologous peripheral blood mononuclear cell (PBMNC) concentrates. The PBMNCs were enriched for lymphocytes using density gradient separation, which were used for CAR T‐cell culture initiation. T‐cell expansion was stimulated with soluble anti‐CD3 and interleukin‐2. RESULTS: Fifty‐one CAR T‐cell products were evaluated; 28 anti–B‐cell maturation antigen (BCMA) CAR T cells produced for 24 patients and 27 CD19 CAR T cells produced for 24 patients. CAR T‐cell expansion was reduced when greater quantities of monocytes were present in the post–density gradient separation PBMNCs. In addition, the ratio of CD4 to CD8 cells in the CAR T‐cell products after 7 days of culture was dependent on the quantity of monocytes, RBCs, and neutrophils in the post–density gradient separation PBMNCs. Greater quantities of monocytes and RBCs were associated with a greater proportion of CD4+ cells and greater quantities of neutrophils were associated with a greater proportion of CD8+ cells. CONCLUSIONS: The composition of leukocytes used to manufacture CAR T cells can affect cell expansion and the composition of CAR T‐cell products. More uniform or complete lymphocyte enrichment of PBMNCs improves the consistency of final CAR T‐cell products.